Human memory - Radvansky, Gabriel A., ....- (Boston (Mass.) : Pearson education, 2011)
Provides students with a guide to human memory, its properties, theories about how it works, and how studying it can help us understand who we are and why we do the things that we do. For undergraduate courses in Human Memory.
Includes bibliographical references and index.
Keywords: Geheugen; Memory